How is Industry 4.0 Changing Food Technology? A Scientometric Profile - Rahaman, Jiaur; Batcha, M Sadik (Journal of Data Science, Informetrics, and Citation Studies)
The food industry has changed due to the present industrial revolution, industry 4.0. The processes taking place in energy and food firms leverage aspects of the industry 4.0 paradigm, such as machine learning, the Internet of Things, and Big Data. The goal of this research is to give academics a summary of works that have been published on the topic of food technology. Hence, the review examines the most active authors, sources, organizations, and countries conducting studies in the subject domain. The selected documents from the Web of Science from 2013 to 2021, using Bibliometrix and VOSviewer software to gather relevant publication trends and identify the most significant networks. The results identified that the growth of food technology literature has many documents published in 2021. A total of 2529 documents were published in 527 sources, among which the most popular was Sustainability. Collaboration among authors reached 91 countries, the most prominent country was China. This research will be a vital tool for academics and policymakers in providing well-developed and better-oriented continuous training programs to lessen the skill gap between workers and jobs.
Keywords: Scientometric; Industry 4.0; Food technology; Web of Science; Bibliometrix tool.